1982
DOI: 10.1002/art.1780250808
|View full text |Cite
|
Sign up to set email alerts
|

Frequencies of epstein‐barr virus—inducible IgM anti‐IgG B lymphocytes in normal children and children with juvenile rheumatoid arthritis

Abstract: The relative frequencies of IgM antiIgG autoantibody (rheumatoid factor) producing cells induced by the polyclonal B cell activator Epstein-Barr virus were measured in peripheral blood lymphocyte cultures of normal children and patients with juvenile rheumatoid arthritis. The frequencies of rheumatoid factor precursor B cells in normal children were lower than adults, but higher than neonates. The frequency increased with the age of the donor. In seronegative children with the systemic-onset or pauciarticular-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1984
1984
2009
2009

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 22 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…However, the EBV has not been as extensively examined in relation to JIA. The outcomes of three small studies seeking evidence of an increased frequency of the EBV infection in JIA have been conflicting [47][48][49]. In 2002, Massa et al [28] examined the interaction between the HLA type and EBV infection in oligoarticular JIA.…”
Section: Infectionmentioning
confidence: 99%
“…However, the EBV has not been as extensively examined in relation to JIA. The outcomes of three small studies seeking evidence of an increased frequency of the EBV infection in JIA have been conflicting [47][48][49]. In 2002, Massa et al [28] examined the interaction between the HLA type and EBV infection in oligoarticular JIA.…”
Section: Infectionmentioning
confidence: 99%
“…These data suggested that by young adult hood the expansion of IgM RF autoantibody precursor cells had occurred, only to be ex pressed after stimulation with an exogenous B cell activator. This was confirmed by a direct analysis of the number of IgM RF-producing B cells in children [16]. Normal, healthy children had EBV-inducible RF pre cursor B cell frequencies lower than adults, but higher than neonates ( fig.…”
Section: Age-associated Expression O F Two Human Autoantibodiesmentioning
confidence: 48%
“…The mechanism of onset of SS is unknown, but some reports have suggested the participation of Epstein-Barr virus (EBV). For example, EBVcauses polyclonal activation of B cells (2)(3)(4), EBV can establish B cell lines positive for EBVassociated nuclear antigen (EBNA), which is expressed spontaneously (that is, without stimulation) by peripheral lymphocytes in SS (3), histopathological changes in SS resemble those in epipharyngeal carcinoma (5), and anti-SS-B antibody forms deposits with cytoplasmic proteins containing EBV-encoded RNA (6). We encountered a patient with rheumatoid arthritis (RA) who developed SS after repeated infectious mononucleosislike symptomsduring the course of RA, and in whom reactivation of EBVwas suspected to have participated in the onset of SS.…”
Section: Introductionmentioning
confidence: 99%